Focal therapy for localized cancer: a patent review. (3rd August 2021) - Bloemberg, Jette; Van Riel, Luigi; Dodou, Dimitra; Breedveld, Paul
ABSTRACT: Introduction: Conventional cancer treatments such as radical surgery and systemic therapy targeting the organ or organ system might have side effects because of damage to the surrounding tissue. For this reason, there is a need for new instruments that focally treat cancer. Areas covered: This review provides a comprehensive overview of the patent literature on minimally and noninvasive focal therapy instruments to treat localized cancer. The medical section of the Google Patents database was scanned, and 128 patents on focal therapy instruments published in the last two decades (2000–2021) were retrieved and classified. The classification is based on the treatment target (cancer cell or network of cancer cells), treatment purpose (destroy the cancerous structure or disable its function), and treatment means (energy, matter, or a combination of both). Expert opinion: We found patents describing instruments for all groups, except for the instruments that destroy a cancer cell network structure by applying matter (e.g. particles) to the network. The description of the different treatment types may serve as a source of inspiration for new focal therapy instruments to treat localized cancer.